Comparison of thiafentanil-azaperone and etorphine-azaperone for the immobilisation of free-ranging black rhinoceros (Diceros bicornis) - O'Dell, Jacques (University of Pretoria, 2025)
Dissertation (MMedVet (Wildlife Disease))--University of Pretoria, 2024.